Dhaka city drivers’ community knowledge, attitude and practice on water, sanitation and hygiene and associated factors: a descriptive cross-sectional study - M., Yahya F. S.; Shamsal, Islam M. (International Journal Of Community Medicine And Public Health, 2021)
Background: Water, sanitation and hygiene (WASH) is to consider the first step to improving the public health of urban people. Primary health-related risk factors are largely induced by urban people's daily WASH practice and this is the leading cause of mortality and disability-adjusted life-years (DALYs) globally. About 28% of Bangladeshi people are living in urban areas and the megacity Dhaka accounts for around 40% of the urban population. In this explanatory research, we explored the knowledge, attitude and practice on WASH and associated factors of drivers’ communities in Dhaka, Bangladesh. Methods: The study was an observational descriptive cross-sectional study and both quantitative and qualitative data were collected. The study was conducted between 03 September 2020, and 28 February 2021. A total of 109 drivers, 8 focus group discussions (FGDs) and 8 key informant interviews (KIIs) were also conducted. Results: The vast majority of drivers were middle age and a few were younger. The vast majority of drivers were experienced and the current job duration was about 7.94±8.33 years. The majority of drivers usually passed leisure time by playing ludo, chess, carrom, cards, chatting online on Facebook (FB), watching the drama on YouTube, watching television (TV), hearing radio programs and gossiping with colleagues. Two-third of the drivers disposing of food waste in the dustbin, and one-third kept inside the vehicle aiming to dispose of it dustbin although some of them throw it into the street. Conclusions: Study findings suggested that there is a need to create WASH facilities and intensive campaigns on hygiene and sanitation to create awareness among aged drivers to practice health and hygiene during duty hours.